NAVIGATION APP (CIPEEX, 2022)
CURRENTLY, LARGE AMOUNTS OF POTHOLES ARE FOUND ON THE STREETS THAT COULD BE FIXEDBUT END UP BEING IGNORED, GENERATING SOME ACCIDENTS THAT COULD BE AVOIDED WITHA WELL-ASPHALTED ROAD, NOT ONLY THAT, BUT WE ALSO KNOW HOW ANNOYING IS TO FACESIGNIFICANT TRAFFIC, WHEN YOU ARE GOING TO WORK FOR EXAMPLE. THEREFORE, THENAVIGATION APP INITIATIVE IS TO USE THE MOST ADVANCED SOFTWARE ENGINEERINGTECHNOLOGIES TO REDUCE THE NUMBER OF POTHOLES ON ROADS AND SHORTEN THE TRAVELTIME FROM ONE DESTINATION TO ANOTHER. SUCH METHODS WERE BASED ON THE BESTMETHODOLOGIES APPLIED WITHIN SOFTWARE ENGINEERING, SUCH AS BPMN, DESIGNTHINKING, AND SCRUM, FOR EXAMPLE. THE PURPOSE OF THIS SOFTWARE IS TO PROVIDE AWAY TO FACILITATE THE USER'S NAVIGATION ON THE ROADS. THE PROJECT WAS CARRIED OUTMAINLY THROUGH AGILE METHODOLOGIES SUCH AS SCRUM AND KAMBAM, SPRINTS, DAILYSCRUM AND REVIEW, AND PROGRAMMING TECHNIQUES. THE RESULTS BASED ONDIFFERENT DISCIPLINES, SUCH AS OOP, DATABASE, AND DATA STRUCTURE DEMONSTRATETHAT THE APPLICATION IS CONSTANTLY DEVELOPING, SEEKING TO IMPROVE ROADS AND TIMESPENT IN TRANSIT THROUGH TECHNOLOGY AND SOFTWARE ENGINEERING.
Keywords: technology; potholes; traffic; agile methodologies